Targeting the Aspergillus flavus p2c gene through host-induced gene silencing reduces A. flavus infection and aflatoxin contamination in transgenic maize - Raruang, Yenjit; Omolehin, Olanike; Hu, Dongfang; Wei, Qijian; Promyou, Surassawadee; Parekattil, Lidiya J.; Rajasekaran, Kanniah; Cary, Jeffrey W.; Wang, Kan; Chen, Zhi-Yuan (Frontiers in Plant Science, 2023)
Maize is susceptible to Aspergillus flavus infection, and subsequent contamination with aflatoxin. Biocontrol and developing resistant cultivars to reduce aflatoxin contamination have only achieved limited success. In the present study, host-induced gene silencing (HIGS) was employed to mitigate aflatoxin contamination in maize by suppressing the expression of the A. flavus p2c gene that encodes a polygalacturonase, a key enzyme involved in the colonization of maize kernels. An RNAi vector containing a portion of the p2c gene was constructed and introduced into maize B104 immature embryos through Agrobacterium transformation. Twenty-eight transgenic plants were produced from fifteen independent transformation events. Thirteen events were confirmed positive for transformation. The kernels containing the p2c transgene from six events out of eleven of T2 generation examined had less aflatoxin than those without the transgene. Homozygous T3 transgenic kernels from four events also produced significantly less aflatoxins (P≤0.02) than the kernels from the null or B104 controls under field inoculation conditions. Six elite inbred lines were crossed with pollens from two of the events and the F1 kernels from the resulting crosses also supported significantly less aflatoxins (P≤0.02) than those from the crosses with pollens from non-transgenic plants. In addition, significantly higher levels of p2c gene-specific small RNAs were detected in the transgenic leaf (T0 and T3) and kernel tissue (T4). Significantly less fungal growth (27~40 fold) was detected in homozygous transgenic maize kernels than in the null control kernels 10 days after fungal inoculation in the field, indicating that the reduced aflatoxin production in the homozygous transgenic kernels is likely due to suppression of p2c expression through HIGS, which results in reduced fungal growth.